Analisis Faktor Penentu Purchase Intention Produk Kosmetik Halal pada Konsumen Generasi Z - Sophiyanto Wuryan; Hawwah Arrayyan (ARZUSIN, 2025)
This study is motivated by the growing importance of understanding consumer behavior in the rapidly expanding halal cosmetics market, particularly among Generation Z. The objective of the research is to analyze the factors influencing purchase intention toward halal cosmetic products in Indonesia, focusing on the variables of religious belief, ingredient safety, halal logo, and promotion. A quantitative approach with a survey method was employed, involving 200 Generation Z respondents who completed an online questionnaire. Data were analyzed using multiple linear regression to identify the effect of each variable on purchase intention. The findings reveal that all four variables have a positive and significant influence on the purchase intention of halal cosmetic products. These results confirm that religious values, ingredient safety, the presence of a halal logo, and effective promotional strategies play crucial roles in shaping consumer intention. The study concludes that halal cosmetic companies should design integrated marketing strategies, particularly by leveraging digital platforms aligned with the characteristics of Generation Z. The implications of this research offer valuable insights for developing business strategies that are grounded in halal values and tailored to the preferences of young consumers in the digital age.